24 Factors associated with emergency ambulance re-attendance within 24 hours of being discharged at scene. (26th April 2019) - Andrew, E; Nehme, Z; Bernard, S; Cameron, P; Smith, K
Abstract : Background: The factors associated with emergency ambulance re-attendance after being discharged at scene by paramedics are poorly understood. Method: Retrospective observational study of consecutive patients attended but not transported to hospital by an emergency ambulance in Victoria, Australia between 01/07/2016 and 30/06/2017. Rates of re-attendance within 24 hours were examined using probabilistic matching. Adjusted logistic regression analyses were performed to determine factors associated with: 1) re-attendance; 2) re-attendances involving cardiac arrest or 'lights/sirens' transport to hospital. Results: There were 97 061 non-transported patients of whom 3393 (3.5%) were re-attended within 24 hours. The outcome following initial attendance was: refused transport against paramedic advice (33.5%); referred to another healthcare provider (17.4%), and; discharged at scene (49.1%). On re-attendance, cardiac arrest occurred in 15 (0.5%) patients of which three were palliative, and 117 (3.4%) required 'lights/sirens' transport. The rate of cardiac arrest or 'lights/sirens' transport was higher in patients who initially refused transport against paramedic advice (4.8% vs. 3.4%, p=0.04). In the multivariable models, older age (Odds Ratio[OR]=1.02[1.01–1.02] per year), male gender (OR=1.25[1.15–1.35]), and an initial alcohol/drug-related issue (OR=1.50[1.05–2.14]) were associated with re-attendance within 24 hours. Older age (OR=1.02[1.01–1.03]), male gender (OR=1.69[1.12–2.55]), an initial pulse rate ≥120 pbm (OR=2.49[1.22–5.06]) and an initial respiratory rate >30 bpm (OR=3.42[1.43–8.14]) were independently associated with re-attendances involving cardiac arrest or 'lights/sirens' transport. Paramedic years of experience was not associated with re-attendance. Conclusion: Ambulance re-attendance after discharge at scene is infrequent. Ambulance services may benefit from development of screening tools which identify patients at risk of harm after discharge at scene. Conflict of interest: None. Funding: None.